Regulation of Modern Stores Business Licensing after the Implementation of the Online Single Submission (OSS RBA) System in Buleleng Regency - I Nyoman Farry Indra Prawira; Ni Komang Arini Styawati (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2025)
This research focuses on the regulation of modern stores business licensing after the implementation of the Online Single Submission Risk-Based Approach (OSS RBA) system, particularly concerning the minimum distance requirements between modern stores and traditional markets as stipulated in Peraturan Daerah No. 10 Year 2013 about the Structuring, Development, and Protection of Traditional Markets, Shopping Centers, and Modern Stores in Buleleng Regency. There are cases where modern retail stores have violated the distance provisions despite having obtained a Business Identification Number. This study employs empirical legal research methods with a juridical analysis approach, supported by primary data obtained through interviews, which are then qualitatively analyzed and linked to legal theories, literature, and applicable laws and regulations. The regulation of business licensing for modern retail stores following the implementation of the OSS RBA system is governed by Peraturan Pemerintah No. 5 Year 2021 concerning the Implementation of Risk-Based Business Licensing. Specifically, the structuring of traditional markets, shopping centers, and modern retail stores in Buleleng Regency is regulated under Peraturan Daerah No. 10 Year 2013. The implementation of the OSS RBA system has not accommodated the minimum distance provisions between modern retail stores and traditional markets, resulting in legal violations.